Clinicopathologic characteristics, treatment, and outcomes of tubulointerstitial nephritis and uveitis syndrome in adults: A national retrospective strobe-compliant study. Issue 26 (June 2016) - Legendre, Mathieu; Devilliers, Hervé; Perard, Laurent; Groh, Matthieu; Nefti, Habdelamid; Dussol, Bertrand; Trad, Salim; Touré, Fatouma; Abad, Sébastien; Boffa, Jean-Jacques; Frimat, Luc; Torner, Stéphane; et al.
Abstract : Abstract: Tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare disease, defined by the association of idiopathic acute TINU. The aim of our work was to determine the characteristics of adult TINU syndrome in France, and to assess factors (including treatment) influencing medium-term prognosis. We conducted a nationwide study including 20 French hospitals. Clinical, laboratory, and renal histopathologic data of 41 biopsy-proven TINU syndromes were retrospectively collected. The patients were diagnosed between January 1, 1999 and December 1, 2015. Twenty-five females and 16 males were included (F/M ratio: 1.6:1). The median age at disease onset was 46.8 years (range 16.8–77.4) with a median serum creatinine level at 207 μmol/L (range 100–1687) and a median estimated glomerular filtration rate (eGFR) at 27 mL/min per 1.73 m 2 (range 2–73). Twenty-nine patients (71%) had a bilateral anterior uveitis and 24 (59%) had deterioration in general health at presentation. Moderate proteinuria was found in 32 patients (78%) (median proteinuria 0.52 g/24 h; range 0.10–2.10), aseptic leukocyturia in 25/36 patients (70%). The evaluation of renal biopsies revealed 41 patients (100%) with an acute tubulointerstitial nephritis, 19/39 patients (49%) with light to moderate fibrosis and 5 patients (12%) with an acute tubular necrosis. Thirty-six patients (88%) were treated with oral corticosteroids. After 1 year of follow-up, the median eGFR was 76 mL/min per 1.73 m 2 (range 17–119) and 32% of the patients suffered from moderate to severe chronic kidney disease. Serum creatinine ( P < 0.001, r = −0.54), serum bicarbonate and phosphate levels (respectively, P = 0.01, r = 0.53; and P = 0.04, r = 0.46), and age ( P = 0.03, r = −0.37) at the 1st symptoms were associated with eGFR after 1 year. During the 1st year 40% of patients had uveitis relapses. The use of oral corticosteroids was not associated with a better kidney function but was associated with fewer uveitis relapses ( P = 0.44 and 0.02, respectively). In our study, 32% of patients were suffering from moderate to severe chronic kidney disease after 1 year of follow-up, and 40% had uveitis relapses during this follow-up. This work also suggests that oral corticosteroids are effective for the treatment of TINU syndrome's uveitis.